PENERAPAN PRINSIP PACTA SUNT SERVANDA TERHADAP RESOLUSI DEWAN KEAMANAN PBB MENGENAI NUKLIR IRAN - Fachrudin Sembiring (Universitas Katolik Indonesia Atma Jaya, 2019)
The Security Council is a main organ under the authority of the United Nation which has a major role in maintaining security and world peace. One of the efforts is to detect over all things that could threat the world. One of them is nuclear technology development by a state with no intention of peace. That was happened with Iran. The Council imposed resolutions to Iran. Many of them met failure because of disobedience of Iran. In the end, JCPOA is formed and become a new beginning of the conformity of Iran. The measure of the JCPOA extent to the Resolution No. S/RES/2231 (2015). Iran must comply the resolution in purpose to respect the UN Charter by principle of Pacta Sunt Servanda. Researcher used juridical-normative method with statute approach. Secondary data is used by placing the UN Charter and resolutions of Iran as the main material. The research carried out to find out the point of appointment that Iran has been responsible over it’s nucler technology development. The responsibility is realized with the approval JCPOA by Iran Government to comply with the Resolution No. S/RES/2231 (2015).